HISTPATHOLOGICAL EFFECTS OF METHOTREXATE ON MALE AND FEMALE REPRODUCTIVE ORGANS IN WHITE MICE - Khalil G. Chelab; Saleh K. Majeed (Basrah Journal of Veterinary Research)
The present study was conducted on (40) white mice of approximately the same age (4-6 weeks) and body weight (23-25 gm) for the aim of observing the histopathological changes for male and female reproductive organs due to prolonged treatment (6 months) with anticancer chemotherapeutic agent namely methotrexate. Forty mice were divided into 4 groups (10 mice of each group 5 mice per sex). The first group (low or therapeutic dose group) was received 0.15 mg/kg B.W. The second group (intermediate dose group ) received 0.3 mg/kg B.W. The third group ( toxic dose group ) received 0.45 mg/kg B.W. the fourth group was a control group; it received 0.2 ml buffered physiological saline. All these groups injected intramuscularly, once weekly for 6 months. The results showed that methotrexate can cause suppression of spermatogenesis. In female, methotrexate can cause obvious pathological changes in uteri and ovaries such as reduced endometrial glands and ovarian follicles respectively